The economics of learning: tradeoffs in student teachers' use of multipurpose digital portfolios. Issue 2 (15th March 2023) - Chye, Stefanie; Zhou, Mingming; Koh, Caroline; Liu, Woon Chia
ABSTRACT: Digital portfolios have gained an increasing prominence in teacher education programmes around the world as a consequence of research which purports their multiple benefits to users and of their potential to represent beginning teachers' practices. Despite the current popularity of digital portfolios, the nature of their use is still not well understood. This article explores how student teachers use digital portfolios in a teacher education programme in Singapore from an economics perspective. It posits that the adoption of an economic lens would shed new light on existing understandings and raise awareness of how and why student teachers use digital portfolios the ways they do. Reference to a range of economic concepts would will help to better understand educational outcomes. The article considers the implications of the findings for informing how digital portfolios are implemented and raises issues for consideration in further implementation efforts and in future research.